Unintentional gallium incorporation in InGaN layers during epitaxial growth. (January 2017) - Zhou, Kun; Ren, Huaijin; Ikeda, Masao; Liu, Jianping; Ma, Yi; Gao, Songxin; Tang, Chun; Li, Deyao; Zhang, Liquan; Yang, Hui
Abstract: Unintentional gallium incorporation was observed and investigated in the epitaxial growth of InGaN by metalorganic vapor phase epitaxy. InGaN was grown without intentional gallium precursor and the gallium incorporation rate was found not dependent on TEGa source but was significantly influenced by temperature and TMIn source flow. The source of the unintentional gallium incorporation is confirmed to be from the flow distributor of the reactor. The incorporation mechanism was analyzed to be the diffusion of resultant of transmetalation reaction between TMIn or its decomposed products (for example DMIn) and residual gallium. Due to the unintentional gallium incorporation, the growth rate and indium content of InGaN layer are determined by indium source, gallium source and the growth temperature. Highlights: Unintentional gallium incorporation was observed and investigated in the epitaxial growth of InGaN. The gallium incorporation rate was significantly influenced by temperature and TMIn source flow. The source of the unintentional gallium incorporation is confirmed to be from the flow distributor of the reactor. The gallium originates from transmetalation reaction between indium precursors and residual gallium. The unintentional gallium incorporation influences the growth of InGaN layers.